Revisiting trigonella foenum-graecum l.: pharmacology and therapeutic potentialities - Visuvanathan, Theysshana; Than, Leslie Thian Lung; Stanslas, Johnson; Chew, Shu Yih; Vellasamy, Shalini (MDPI, 2022)
Fenugreek (Trigonella foenum-graecum L.) is a medicinal plant that has been used as a food condiment as well as for its multiple therapeutic characteristics since ancient times. Fenugreek plant grows up to 60 cm in height, and its seeds are golden-yellow rhomboidal-shaped. Though fenugreek is more commonly known for its seeds, the leaves and stem have also been reported to have medicinal uses. These properties exhibited are due to the content of the secondary metabolites, also known as phytochemicals, in the fenugreek plant. Such metabolites are alkaloids, saponins, tannins, phenols, and many others. Fenugreek has been used traditionally for numerous indications, such as aid in labour, lactation stimulant, and laxatives. In modern research, there have been several animal and clinical studies that have shown therapeutic effects of fenugreek when taken orally. Fenugreek is a suitable plant candidate with a high prospect of being used as a credible medicinal plant to derive new drugs. This review aims to summarize the physical and chemical properties of fenugreek and its bioactive compounds that have been isolated for medicinal purposes and discusses the traditional and pharmacological uses of fenugreek.